An observational study of the association among interatrial adiposity by computed tomography measure, insulin resistance, and left atrial electromechanical disturbances in heart failure. Issue 24 (June 2016) - Hung, Chung-Lieh; Yun, Chun-Ho; Lai, Yau-Huei; Sung, Kuo-Tzu; Bezerra, Hiram G.; Kuo, Jen-Yuan; Hou, Charles Jia-Yin; Chao, Tze-Fan; Bulwer, Bernard E.; Yeh, Hung-I.; Shih, Shou-Chuan; Lin, Shing-Jong; et al.
Abstract : Abstract: Excessive visceral adiposity, hypothesized to be a key mediator in metabolic derangements, has recently been shown to exert toxic effects on cardiac structure and function. Data regarding the mechanistic link between regional adiposity, left atrial (LA) electromechanical remodeling, and heart failure with preserved ejection fraction (HFpEF) have been lacking. Various visceral adiposity measures, including pericardial fat (PCF), thoracic periaortic (TAT) fat, regional inter-atrial fat (IAF), and atrioventricular groove fat (AV Groove Fat), were assessed by multidetector computed tomography in 2 study cohorts (an annual health survey cohort and an outpatient cohort). We related such measures to cardiometabolic profiles in health survey cohort and LA electromechanical indices in our outpatient cohort, with Cox proportional hazards performed to examine the temporal trends of heart failure (HF). In our annual health survey cohort (n = 362), all 4 adiposity measures were positively related to unfavorable anthropometrics and systemic inflammation (high-sensitivity C-reactive protein) (all P  < 0.05). In addition, both greater IAF and AV Groove Fat were positively associated with higher fasting glucose, HbA1c levels, and insulin resistance (all P  < 0.05). In the outpatient cohort, the HFpEF group demonstrated the greatest adiposity measures, with greater IAF (≥8.2 mm, hazard ratio: 4.11, 95% confidence interval: 1.50–11.32) associated with reduced LA strain (ß-coef: –0.28), higher LA stiffness (ß-coef: 0.23), and longer P wave duration (ß-coef: 0.23) in multivariate models (all P  < 0.05), and further related to higher HF hospitalization during follow-up. We therefore propose a possible pathophysiologic link among greater visceral adiposity, systemic inflammation, cardiometabolic risks, and HFpEF. Regional adiposity, especially IAF, was tightly linked to altered LA electromechanical properties and likely plays a key role in HF prognosis. Abstract : Supplemental Digital Content is available in the text